Study of Λ0b and Ξ0b decays to Λ⁢h+⁡h′− and evidence for CP violation in Λ0b →Λ⁢K+⁢K− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
A study of Λ0𝑏 and Ξ0𝑏 decays to Λ⁢ℎ+⁡ℎ′− (ℎ(′)=𝜋,𝐾) is performed using 𝑝⁢𝑝 collision data collected by the LHCb experiment during LHC Runs 1-2, corresponding to an integrated luminosity of 9 fb−1. The branching fractions for these decays are measured using the Λ0𝑏→Λ+𝑐⁡(→Λ⁡𝜋+)⁢𝜋− decay as a control channel. The decays Λ0𝑏 →Λ⁢𝜋+⁢𝜋− and Ξ0𝑏 →Λ⁢𝐾−⁢𝜋+ are observed for the first time. For decay modes with sufficient signal yields, 𝐶⁢𝑃 asymmetries are measured in the full and localized regions of the final-state phase space. Evidence is found for 𝐶⁢𝑃 violation in the Λ0𝑏 →Λ⁢𝐾+⁢𝐾− decay, interpreted as originating primarily from an asymmetric Λ0𝑏 →𝑁*+⁢𝐾− decay amplitude. The measured 𝐶⁢𝑃 asymmetries for other decays are compatible with zero.
Im Titel ist "0" , "+" und "-" jeweils hochgestellt - und der Buchstabe "b" jeweils tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascón, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M.D. Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 13.01.2026